PENGARUH PENERAPAN METODE PERMAINAN SUKU KATA TERAKHIR TERHADAP KETERAMPILAN MENULIS PUISI KELAS V MIN - Pitriani, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of the research is to analyse the effect of the usage of the last syllable game method on fifth grade free poetry writing students skills in MIN Southeast Pontianak. The methode that has been used was experimen method with forms of pre experimental design type of experiment one group pretest posttest design. Research population of the entire 4A and 4B consist of 76 students in MIN.. The sample is a VB class of 37 student. The result of the research is the average pre-test score 60,6206, meanwhile post-test 77,6206. t-Test price tcount compared with ttable with dk= 29-1= 28 and significant level (α) 5% obtained ttable price= 2,048, it turns thitung≥ttable or 25,4987≥2,048 means significant, it is concluded that Ho is rejected, on the contrary Ha accepted. Thus it can be concluded that there is influence the use of the last syllable game method on fifth grade free poetry writing students skills in MIN in Southheast Pontianak. The result of the calculations on the effect size in experiment class was 1,31(high criteria). It means that the use of the last syllable game methode gave high influence (effect) toward free poetry writing students skills in MIN in Southeast Pontianak. Keywords: Influence, Last Syllable Game, Writing Students Skills